VD_FINDINFO Jug / 2015 / 79 vom 19. November 2014 - VD Tribunal cantonal (2014)
EXCÈS DE VITESSE, À L'INTÉRIEUR DES LOCALITÉS, ERREUR SUR LES FAITSDROIT PÉNAL, MARQUESIGNALISATION ROUTIÈRE | 13 CP, 27 al. 1 LCR, 90 al. 2 LCR, 4a al. 1 OCR, 4a al. 2 OCR